(untitled) (Journal of Engineering, 2013)
Research covers the uses the method of Quality Rating Evaluation to evaluate the quality of production through which a determination of product quality of its production in order to determine the amount of sales hence the profits for the company. The most important function is to satisfy consumer at reasonable prices. Methods were applied to the product (toothpaste) in the General Company for Vegetable Oil – Almaamoon Factory . The company’s has obtained ISO-certified (ISO 9001-2008). Random samples of final product intended for sale were collected from the store during months (February, April , June , October and December) for the year 2011 to determine the "quality rating " through the application of the method on the products at final stage , where selected. The properties that affect product quality and varieties of defects for each property (A, B, C , D) and give the points of on rejects . The research concluded that the percentage of output quality for the product toothpaste (AMBER) weighing 75 g ranges between (70-80%) is within quality level which is good in condition and that the company’s plan was effective and influential in the development of its products. In addition to the significant improvement in the level of quality and process productivity statistically controlled and the results were within the limits of the chart quality control .Also it was found that is was within Iraqi specification (1100)